Desain Shell and Tube Heat Exchanger (STHE) Tipe Counter Current dengan Material Stainless Steel - Eka Cahya Muliawati (Institut Teknologi Adhi Tama Surabaya, 2022)
A heat exchanger or commonly referred to as a heat exchanger is a tool that is commonly used in the industrial world. The function of this tool is to cool down a fluid. There are various types of heat exchangers, including shell and tube. The purpose of this research is to design a heat exchanger that is good and correct and has a fairly high effectiveness in accordance with the existing heat exchanger design rules. The object of this research is a heat exchanger with a size of OD in, 16 BWG with stainless steel material which has a counter current type which is used to cool the type of air at a temperature of 80°C to 60°C with the help of an air type fluid also at a temperature of 60°C. 30°C. The effectiveness of the tool is quite large, namely 88.7%.